(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article describes that due to deep reforms in the education system, qualified teaching staff working in the field of higher pedagogical education are constantly engaged in creative work aimed at improving their skills, and opportunities for accelerating scientific activities are expanding.